Conservative surgical management of large bilateral mandibular odontogenic keratocyst: a case report and literature review - Tulsi, S. P. S.; Singh, Sujeet; Pandey, Praveen K.; Garg, Kavita N.; Singh, Shalvi (International Journal of Research in Medical Sciences, 2025)
Odontogenic keratocyst (OKC) have a been a controversial topic within the medical, research and taxonomy community. It is because of these controversies this requires our special attention. From a clinician’s view, its varied presentation and high recurrence rate makes it special. One possible explanation for such high recurrence is the presence of anti-apoptotic gene; BCL-2 in high concentration in the epithelial lining of OKCs. Even rarer is its presentation bilaterally, we present one such case of a young male. After facing multiple misdiagnosis and any significant improvement, he was finally diagnosed on the basis of biopsy and underwent serial marsupialization followed by enucleation. We present this case to stress on the fact that conservative surgical management by marsupialization under local anaesthesia itself is enough without the need of costly reconstruction in cases with unilocular cyst involving the mandible bilaterally with review of relevant literature.